Conspicuous consumption, economic growth, and taxation: A generalization - Walter H. Fisher; Franz X. Hof (Institute for Advanced Studies (IHS), 1999)
This paper studies the influence of consumption externalities in the Ramsey model. In contrast to the recent literature, a quite general specification of preferences is used and the concept of the effective intertemporal elasticity of substitution is introduced. We give conditions for the observational equivalence between economies with consumption externalities and externality-free economies. An additional key result is that there exist several types of instantaneous utility functions in which the decentralized solution coincides with the socially planned one in spite of the presence of consumption externalities. The conditions for optimal taxation are also derived.
Keywords: D62; D91; E21; E62; 330; social status; conspicuous consumption; economic growth